An introduction to Third World theologies - Parratt, John (Introduction to religion., 2004)
Providing an overview of the main trends and contributions to Christian thought of Third World theologies, this book gathers essays from experts on Latin America, India, East Asia, West and East Africa, Southern Africa and the Caribbean. It analyzes the common context of the Third World theologies in their experience of colonialism and Western missions, and suggests that they provide different perspectives on what it means to be a Christian in today's world. --From publisher's description.